Two-parameter model of optimization of the progressive taxation system and its applicability - Slepov, Vladimir Alexandrovich; Grishina, Olga Alekseevna; Kosov, Mikhail Evgenievich; Khoranyan, Mikael Edvardovich; Balandin, Sergey Aleksandrovich (Nexo Revista Científica, 2022)
The work aims to develop a model of income taxation that allows strengthening the fiscal effect of personal income tax and reducing the differentiation of income levels of different segments of the population, as well as assessing the impact of the proposed model on social inequality in Russia. To achieve this goal, a special two-parameter model of progressive income tax was developed, reflecting the result of studying the features of modern Russian taxation in the context of personal income tax. The key advantage of the developed tax model is the ability to assess social differentiation (by income category) in a pairwise subdecile breakdown, which allows the state to conduct a more balanced policy concerning each of the income groups participating in the study, which can be expressed, for example, in granting special tax preferences to decile groups that need it.